СУЛЬФАТЫ КОБАЛЬТА ИЗ МЕДНО-КОЛЧЕДАННОГО МЕСТОРОЖДЕНИЯ ЛЕТНЕЕ (ЮЖНЫЙ УРАЛ) - Белогуб Е.В.; Щербакова Е.П.; Мороз Т.Н.; Новоселов К.А. (My University, 2005)
Co-bearing sulfates: bieberite (Co0.48Zn0.22Cu0.25Fe0.03Mg0.02)(SO4)·7H2O, moorhouseite (Co0.49Zn0.24 Cu0.20Fе0.04Mg0.03)(SO4) 6H2O and cobaltkieserite (Co0.40Zn0.37Cu0.20Mg0.03)(SO4) H2O, were found in products of contemporary weathering of the Letneye copper massive sulfide ore deposit (Orenburg region, Russia). These sulfates form thin zonal pink crusts on the surface of oxidized ores and clayey altered host rocks. They associate with chalcantite and Zn-sulfates: goslarite: (Zn0.47Cu0.21MgO0.16Fe0.08Co0.08)SO4 7H2O and bian-chite (Zn0.49 Co0.27Cu0.23)SO4 6H2O. Bieberite occurs as transparent pink-reddish long-prismatic crystals, up to 2-3 mm in length, inside the sulfate crusts. Moorhouseite forms semi-transparent pink-cream-colored spherules in the lower zones of the sulfate crusts, their top zones consist of non-transparent pink parallel-columnar, fibrous or earthy aggregates of cobaltkieserite. Under dehydration, noncolored or white goslarite and bianchite arc getting pinkish. The Co-bearing sulfates were studied chemically, by X-ray analysis and SEM; their formation on the evaporation barrier is connected with advanced oxidation of the Co-bearing pyrite and cobaltite, which were found as major concentrators of cobalt in ores of Letneye deposit. It would be emphasized that characteristic features of these minerals are the high amounts of Zn in cobalt sulfates, the high amount of Co in zinc sulfates and, in addition, the regular presence of copper, so that their ideal compositions may be described as (Co,Zn,Cu) SO4 · nН2О and (Zn,Co,Cu)SO4 · nН2О where n is 1, 6 or 7. There haven't been found any bi- or tet-rahydrates.
Keywords: 549.76661.873.622.791